Conceptual Framework. - Breuste, Jürgen; Li, Junxiang; Grunewald, Karsten (Springer, 2018)
A conceptual approach for greener cities must always be based on recognized actual and expected challenges. A first reaction is to develop strategies to deal with these challenges. These strategies have to be conceptualized in clear, targeted concepts. This is the main idea of the chapter and of the book as a whole. Doing this for two very different countries, different in size, population, and urbanization level, is a challenge of its own. The need to come to positive results may be much more challenging in China than in Germany. But the strategies can be readily compared, and the two sides can learn from each other about the efficiency of strategies and concepts.
Keywords: Stadtentwicklung; Ökologie; Nachhaltige Entwicklung; Konzeption; Politik; Stadtverwaltung; Transformation; Landschaftsverbrauch; Flächennutzung; Stadtgrün; Landnutzung; Stadtökologie; Stadtnatur; Biodiversität; Ökosystem; Vergleichsuntersuchung